Smart villages concept — A bibliometric analysis and state-of-the-art literature review - Bokun, Katarzyna; Nazarko, Joanicjusz (Progress in planning, 2023)
Rural areas are multidimensional and complex structures. The multitude and spatial diversity of processes occurring in their internal and external environment challenges the creation of a uniform and comprehensive approach to planning their development. The smart village concept, which has been gaining popularity in recent years, is supposed to answer the needs of contemporary rural areas. Essentially, it uses the area’s potential, considers its specificity, involvement of the local community in the process of change, and the rational use of new and existing technologies. Despite its growing popularity, the concept is in the early formulation stage. This article determines the current state-of-the-art of the smart village concept based on a bibliometric analysis of scientific articles collected from the Web of Science, Scopus, and IEEE Xplore databases and on a qualitative document analysis of the major smart village initiatives. The bibliometric analysis included 351 articles published until the end of 2021. Qualitative document analysis was performed on nine initiatives implemented in different world regions. As a result, detailed bibliometric metrics of the global smart village publication output were presented, characterizing the development and current state of the smart village concept. The authors point out the multidimensionality of the concept, propose its contemporary definition, and identify its basic dimensions: people, economy, living, energy, environment, mobility, and governance, thus creating a methodological basis for the planning, design and implementation of smart village projects. •Smart village concept does not have a single, universal, and consistent definition.•Dimensions of “Smart village” are: people, economy, living, energy, environment, mobility, and governance.•The essence of “Smart village” is the ability to manage available resources and meet the needs of the local community.